PERIOPERATIVE COMPLICATIONS AND REMOTE RESULTS OF PERCUTANEOUS CORONARY INTERVENTIONS IN PATIENTS WITH STABLE ANGINA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - V. K. ZAFIRAKI; E. D. KOSMACHEVA (Кубанский научный медицинский вестник, 2017)
Aim. To estimate the frequency of hospital complications and the long-term (duration of observation to 3 years) results of percutaneous coronary interventions (PCI) performed for stable effort angina in patients with chronic obstructive pulmonary disease (COPD). Materials and methods. Hospital complications were recorded after PCI in a series of 605 patients with stable effort angina with a history of long-term smoking, among which 142 patients with COPD were identified by spirography. For the prospective part of the study, 135 COPD patients and 216 patients in the control group were selected. During long-term follow-up (up to 3 years), the incidence of major cardiovascular events (MACCE) was recorded. Results. No effect of COPD on the incidence of hospital complications after PCI was found. The relative risk (RR) of major cardiovascular events in the long-term period was 1.36 (95% confidence interval 0.97-1.90). RR of revascularization was 1.77 (95% confidence interval 1.11-2.82). Conclusion. COPD does not affect the incidence of hospital complications after PCI, but increases the risk of MACCE in the long-term, mainly due to repeated myocardial revascularization.